Development and Validation of a Novel Real-time Assay for the Detection and Quantification of Vibrio cholerae - Rashid, Ridwan Bin; Ferdous, Jannatul; Tulsiani, Suhella; Jensen, Peter Kjaer Mackie; Begum, Anowara (Frontiers in Public Health, 2017)
Vibrio cholerae O1 and O139 has been known for its ability to cause epidemics. These strains produce cholera toxin which is the main cause of secretory diarrhea. Vibiro cholerae non O1 and non O139 strains are also capable of causing gastroenteritis as well as septicemia and peritonitis It has been proven that virulence factors such as T6SS, hapA, rtxA, hlyA are present in almost all Vibrio cholerae strains . It is imperative that viable but non culturable (VBNC) cells of Vibrio cholerae are also detected since they are also known to cause diarrhea. Thus the aim of this study was to develop an assay that detects all Vibrio cholerae regardless of their serotype, culturable state and virulence gene present, by targeting the species specific conserved ompW sequence. The developed assay meets these goals with 100% specificity and is capable of detecting as low as 5.46 copy number. Detection is rapid since neither lengthy incubation period nor electrophoresis is required. The assay had excellent repeatability (CV%: 0.24-1.32) and remarkable reproducibility (CV%: 1.08-3.79). Amplification efficiencies in the 89-100 % range were observed. The assay is economical since it is based on SYBR green and only one primer pair is needed. Compared to other real-time assays, the ompW assay is specific and sensitive, has better repeatability, reproducibility and is more economical.